1996
DOI: 10.1093/clinids/23.5.1162
|View full text |Cite
|
Sign up to set email alerts
|

Association of Athlete's Foot with Cellulitis of the Lower Extremities: Diagnostic Value of Bacterial Cultures of Ipsilateral Interdigital Space Samples

Abstract: We performed a study to determine how often patients with cellulitis of the lower extremities in the absence of trauma, peripheral vascular disease, or chronic open ulcers have ipsilateral interdigital athlete's foot and whether cultures of samples from the involved interdigital spaces would yield potentially pathogenic bacteria. Athlete's foot was present in 20 (83%) of 24 episodes of cellulitis that were studied. Cultures of samples from interdigital spaces yielded Beta-hemolytic streptococci in 17 (85%) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(53 citation statements)
references
References 11 publications
3
49
0
Order By: Relevance
“…The growth of Gram-negative bacilli and Staphylococcus aureus was similar in the two patient populations. 1 The bacteria may cause cellulitis by entering the skin at these sites or by spreading to contiguous cutaneous surfaces and invading through a disrupted epidermis or through areas of impaired local defenses. This correlation aims to emphasize the importance of seeking and treating tinea pedis, so as to prevent recurrent episodes of cellulitis, which are common in patients who have had a previous attack.…”
Section: Commentsmentioning
confidence: 99%
“…The growth of Gram-negative bacilli and Staphylococcus aureus was similar in the two patient populations. 1 The bacteria may cause cellulitis by entering the skin at these sites or by spreading to contiguous cutaneous surfaces and invading through a disrupted epidermis or through areas of impaired local defenses. This correlation aims to emphasize the importance of seeking and treating tinea pedis, so as to prevent recurrent episodes of cellulitis, which are common in patients who have had a previous attack.…”
Section: Commentsmentioning
confidence: 99%
“…3,4 Sites of entry are commonly created by traumatic injury, leg ulcers, and possibly, dermatophytic toe web intertrigo. [3][4][5] Two recent case-control studies addressing risk factors for cellulitis demonstrated a significantly higher rate of toe web intertrigo in the patient group. 3,4 Although dermatophytes do not cause cellulitis, they lead to scaling and fissure formation and, by disruption of the skin, provide a niche for bacteria that could enter the body.…”
Section: Introductionmentioning
confidence: 97%
“…1,2 Various risk factors for cellulitis include traumatic injury, leg ulcers, intertrigo, overweight, lymphedema, diabetes mellitus, vasculitis, previous surgery, radiotherapy and immunocompromised states. 2,3 Causative organisms for cellulitis include Streptococcus pyogenes and Staphylococcus aureus followed by β hemolytic streptococci and gram negative bacilli. 4,5 Exact incidence of cellulitis in India is unknown but in USA, it is a common infection affecting 2-3 persons/100 persons/year.…”
Section: Introductionmentioning
confidence: 99%